The Role of Medical Thoracoscopy for the Diagnosis and Treatment of Unexplained pleural effusion: a single center experience over one year - Rashid, Md Mamunur; Islam, Mohammad Azharul; Huq, Masrura; Naznin, Bidoura; Afroz, Shahrin (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Medical Thoracoscopy (MT) is a minimally invasive endoscopic procedure that allows almost complete visualization of pleural cavity, collection of appropriate amount of samples and to do necessary work for the treatment of pathologies. MT is gaining popularity world-wide and few centers in Dhaka practicing it. Here, this study observed the utility of MT in a single centre in a single calendar year. Methods: It was a retrospective study done at respiratory medicine center of a tertiary care hospital, Dhaka reviewing records of all cases of medical thoracoscopy (MT) done as a diagnostic and/or therapeutic procedures over one year. After collecting data, we analyzed them to see the indications, pre- and post-procedural status, outcomes and safety of this procedure. Results: Total 16 patients with unexplained pleural effusion were undergone medical thoracoscopy (MT) last year in Square Hospital. All 16 had diagnostic MT and 7 had therapeutic MT as well. Among all 16 patient, 3 patients were from Oncology, 2 from intensive care unit, 1 from gastroenterology unit and 1 from nephrology unit, others were from our inpatients. MT revealed malignancy in 7 cases (43.75%), tuberculosis in 4 (25%), complicated multiloculated empyema in 3 cases (18.75%), hepatic and renal hydrothorax in 1 case respectively. Among malignant cases, bronchial carcinoma predominates, followed by breast cancer (1 patient) and uterus (1 patient). Pleural adhesionolysis and deseptation was done in 5 cases and pleurodesis by talc slurry or poudrage in 4 cases. There was no major adverse effect seen at or after the procedure. Pain due to chest tube was the main adverse-effect which was managed with simple analgesics. One patient had mild reperfusion pulmonary edema which was easily managed with perenteral steroid for 3 days. One patient had bronchopleural fistula which was managed with repeated tetracycline pleurodesis. All patients were managed effectively with only 2 patients shown to have minimal residual effect like pleural thickening. Conclusion: Medical thoracoscopy or pleuroscopy is a safe and very effective procedure for the diagnosis of the primary etiologies of unexplained pleural effusion and their management. J Bangladesh Coll Phys Surg 2025; 43: 277-293